2005
DOI: 10.1523/jneurosci.2454-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of TASK Channels between Horizontal Interneurons and Pyramidal Cells of Rat Hippocampus

Abstract: Among the electrophysiological properties differentiating stratum oriens horizontal interneurons from pyramidal neurons of the CA1 hippocampal subfield are the more depolarized resting potential and the higher input resistance; additionally, these interneurons are also less sensitive to ischemic damage than pyramidal cells. A differential expression of pH-sensitive leakage potassium channels (TASK) could contribute to all of these differences. To test this hypothesis, we studied the expression and properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 55 publications
(100 reference statements)
5
54
2
Order By: Relevance
“…Attempts to determine the TASK-3 content of other neurochemically defined populations of interneurons was equivocal and suggests that TASK-3 is largely expressed in parvalbumincontaining, and a subpopulation of somatostatin-containing interneurons. Importantly, these data indicate that TASK-3 protein is expressed in a greater number of CA1 interneurons than suggested previously (Taverna et al 2005). …”
Section: Task-3 Is Primarily Expressed In Parvalbumin-positive Cellssupporting
confidence: 69%
See 3 more Smart Citations
“…Attempts to determine the TASK-3 content of other neurochemically defined populations of interneurons was equivocal and suggests that TASK-3 is largely expressed in parvalbumincontaining, and a subpopulation of somatostatin-containing interneurons. Importantly, these data indicate that TASK-3 protein is expressed in a greater number of CA1 interneurons than suggested previously (Taverna et al 2005). …”
Section: Task-3 Is Primarily Expressed In Parvalbumin-positive Cellssupporting
confidence: 69%
“…TASK channel expression in SO interneurons has been previously investigated by Taverna et al (2005), who concluded that TASK-like currents are not consistently detectable in horizontal CA1 SO interneurons, and only ϳ15% of CA1 SO interneurons express TASK-3 mRNA. However, in the present study, ϳ50% of morphologically identified horizontal interneurons displayed a TASK-like current.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The developmental reduction in R m could be explained by increases in densities of leak channels (e.g., two-pore domain K ϩ channels) (Taverna et al, 2005;Torborg et al, 2006). Changes in morphology and membrane properties jointly redefine somatodendritic integration of EPSPs in BCs.…”
Section: Developmental Changes In Bc Morphologymentioning
confidence: 99%